Silicon incorporation in polymethine dyes. Issue 45 (1st May 2020) - Pengshung, Monica; Neal, Patrick; Atallah, Timothy L.; Kwon, Junho; Caram, Justin R.; Lopez, Steven A.; Sletten, Ellen M.
Abstract : Incorporation of silicon into heterocycles for polymethine dyes can impart red-shifts of up to 100 nm, while also enhancing photostability up to 10-fold, resulting in photostable fluorophores with emission above 900 nm. Abstract : Methods to red-shift fluorophores have garnered considerable interest due to the broad utility of low energy light. The incorporation of silicon into xanthene and coumarin scaffolds has resulted in an array of visible and near-infrared fluorophores. Here, we extend this approach to polymethine dyes, another popular fluorophore class, performing experimental and computational analyses. We found that when oxygen was replaced with SiMe2, bathochromic shifts of up to 121 nm and fluorophores with emission above 900 nm were achieved.